The Role of Corporate Governance in Moderating the Relationship Between Earnings Management and Financial Performance of Public Companies - Nurfitriani Nurfitriani; Ima Amaliah; Nunung Nurhayati (PT. Anagata Sembagi Education, 2025)
This study aims to investigate the role of corporate governance in moderating the relationship between earnings management and the financial performance of public companies. Employing a quantitative approach with a longitudinal panel data design, the research analyzed a sample of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Financial performance was measured by Return on Assets (ROA), earnings management was proxied by discretionary accruals calculated from the Modified Jones Model, and corporate governance was constructed as a composite index from board independence and audit committee characteristics. The data was analyzed using Moderated Regression Analysis (MRA) with panel data. The results indicate that earnings management has a direct negative effect on company performance. Furthermore, the study's core finding confirms that corporate governance significantly moderates this relationship. The positive and significant interaction term demonstrates that strong corporate governance mechanisms effectively weaken the negative impact of earnings management on financial performance. These findings underscore the critical importance of robust corporate governance as a monitoring tool. They provide empirical evidence that effective oversight can mitigate the adverse consequences of earnings management, thereby promoting more transparent financial reporting and contributing to sustainable corporate value.